2023
DOI: 10.3390/info14030140
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tree-Based Machine Learning Algorithms to Predict Reporting Behavior of Electronic Billing Machines

Abstract: Tax fraud is a common problem for many tax administrations, costing billions of dollars. Different tax administrations have considered several options to optimize revenue; among them, there is the so-called electronic billing machine (EBM), which aims to monitor all business transactions and, as a result, boost value added tax (VAT) revenue and compliance. Most of the current research has focused on the impact of EBMs on VAT revenue collection and compliance rather than understanding how EBM reporting behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The introduction of the CG-JKNN model in our study presents new avenues for potential research. The performance of GNN models can be significantly enhanced through knowledge distillation [ 88 ], [ 89 ]. This process could enable the GNN models to require even fewer parameters than XGBoost while delivering comparable performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of the CG-JKNN model in our study presents new avenues for potential research. The performance of GNN models can be significantly enhanced through knowledge distillation [ 88 ], [ 89 ]. This process could enable the GNN models to require even fewer parameters than XGBoost while delivering comparable performance.…”
Section: Resultsmentioning
confidence: 99%
“…While this is the lowest among the models chosen, it still represents a decent level of performance. Feature scaling was omitted in our approach for ML models, as these models are tree-based and inherently robust to scaling [89]. In developing our GNN models, we employed the Standard Scaler technique [90] for feature scaling, as GNN models require scaled features to ensure that each input feature contributes proportionately to the model's learning process [40].…”
Section: Classification Resultsmentioning
confidence: 99%
“…We find some recent publications on transformer models [22][23][24]. In general, all methods have their own biases and assumptions that need to be carefully considered, see for example [25][26][27].…”
Section: Related Workmentioning
confidence: 99%
“…Recent research in digital taxation and AI reveals significant advancements in promoting tax compliance. Bellon et al (2022) and Murorunkwere et al (2023) both demonstrated how digital tools such as electronic invoicing and machine learning algorithms such as random forest effectively improve compliance among businesses and predict value added tax (VAT) compliance. These studies underscore the role of technology in reducing compliance costs and enhancing enforcement.…”
Section: Introductionmentioning
confidence: 99%